PENGETAHUAN FILARIASIS DAN PENGGUNAAN OBAT GOSOK PENGUSIR NYAMUK DI WILAYAH ENDEMIS FILARIASIS - Mutiara Widawati; Muhammad Umar Riandi; Yuneu Yuliasih (Puslitbang Upaya Kesehatan Masyarakat, 2019)
ABSTRACT The uses of repellent are an effort to prevent mosquito bites in the community. Therefore, a study was conducted to find out the difference in the level of knowledge with the use of repellent/liniment on people in areas that received the Filariasis Mass Prevention Drug Program. This research is the result of secondary data analysis from multicenter research